2018
DOI: 10.1063/1.5042533
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton photoelectron circular dichroism of limonene with independent polarization state control of the bound-bound and bound-continuum transitions

Abstract: Photoionization of randomly oriented chiral molecules with circularly polarized light leads to a strong forward/backward asymmetry in the photoelectron angular distribution. This chiroptical effect, referred to as Photoelectron Circular Dichroism (PECD), was shown to take place in all ionization regimes, from single photon to tunnel ionization. In the Resonance Enhanced Multiphoton Ionisation (REMPI) regime, where most of the table-top PECD experiments have been performed, understanding the role of the interme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…[25,26] The influence of polarization state used for excitation and ionization on observed PECD was modeled [26] and investigated experimentally. [27] Using a fs pump-probe setup, dynamics in the 3s intermediate state were investigated for fenchone. [28,29] When the duration of the laser pulses is increased to longer than ps, intra-molecular dynamics in addition to rotation of the molecules can evolve during ionization, where it is not clear whether PECD can be observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[25,26] The influence of polarization state used for excitation and ionization on observed PECD was modeled [26] and investigated experimentally. [27] Using a fs pump-probe setup, dynamics in the 3s intermediate state were investigated for fenchone. [28,29] When the duration of the laser pulses is increased to longer than ps, intra-molecular dynamics in addition to rotation of the molecules can evolve during ionization, where it is not clear whether PECD can be observed.…”
mentioning
confidence: 99%
“…For REMPI studies, changing the laser wave-length allows to study the dependence of PECD on intermediate state and photoelectron kinetic energy [17,[22][23][24] in comparison to theoretical descriptions [25,26]. The influence of polarization state used for excitation and ionization on observed PECD was modeled [26] and investigated experimentally [27]. Using a fs pump-probe setup, dynamics in the 3s intermediate state were investigated for fenchone [28,29].…”
mentioning
confidence: 99%
“…In the three molecular species considered here, the resonant absorption of three photons at 515 nm (2.4 eV) promotes the molecules to high-lying Rydberg states, from which they are photoionized by further absorption of one or several photons. By decoupling the excitation and ionization steps through a two-color experiment, we recently demonstrated that photoexciting molecules with linearly or circularly polarized photons led to strong changes in the PECD, with possible sign inversions 31 . This is the result of the anisotropy of excitation introduced by the resonance.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, understanding the role of the intermediate resonances is subject of experimental and theoretical investigations. Recently it was demonstrated, by decoupling bound-bound and bound-continuum transitions, that the helicity of the light pulse that drives the bound-bound transitions has a negligible effect on the PECD 51,52 . However, circularly and linearly polarized laser pulses still lead to different PECDs because of the angular dependence of the excitation process, which induces different anisotropies.…”
Section: Mechanism 3: Evolution Of the Liberated Electronmentioning
confidence: 99%